Two-Stage Revision of an Infected Total Hip Arthroplasty: A Follow-up of 136 Patients. Issue 5 (September 2013) - van Diemen, Marcus P.J.; Colen, Sascha; Dalemans, Alain A.R.; Stuyck, Jose; Mulier, Michiel
Background and purpose: Periprosthetic infection of a total hip arthroplasty (THA) is commonly treated with a two-stage revision procedure. After resection of the infected THA and placement of a cement spacer loaded with antibiotics, a THA is inserted at a second procedure to restore hip function and mobility. Revision surgery carries a significant risk of complications. This study focuses on hip function, rate of complications and reinfection after two-stage revision surgery for an infected THA. Patients and methods: From January 1996 to April 2010, 136 patients underwent revision surgery after removal of an infected THA. Follow-up ranged from 2 years to more than 15 years. Hip function was evaluated using the modified Harris Hip Score (mHHS) and the Hip disability and Osteoarthritis Outcome Score (HOOS). Visual Analogue Scale (VAS) measured pain. Annual follow-up included radiographs of the affected hip and blood sampling for inflammatory parameters. Results: After revision surgery, average mHHS was 63% and average HOOS was 54%. VAS pain averaged 26.8 on a 100-point scale and 40% of patients had no pain. Prosthesis-related complications unrelated to sepsis occurred in 32%. Most common were periprosthetic fractures, leg length discrepancy and dislocation. Reinfection occurred in 13% of these patients and Coagulase Negative Staphylococcus (CNS) was isolated in 67%. Conclusion: Two-stage revision surgery is an accepted treatment for infected THAs. However, complications are common and hip function afterwards is modest. As previous studies have shown, CNS is an important microorganism in reinfection.